2016
DOI: 10.1515/sjecr-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Subchronic Methionine Overload Administered Alone or Simultaneously with L-cysteine or N-acetyl-L-cysteine on Body Weight, Homocysteine Levels and Biochemical Parameters in the Blood of Male Wistar Rats

Abstract: Hyperhomocysteinemia (HHC), both basal and after methionine load, may occur due to genetic disorders or defi ciencies of nutrients that aff ect the remethylation or transsulphuration pathways during methionine metabolism. HHC is involved in the pathogenesis of many illnesses as a SAŽETAK Hiperhomocisteinemija (HHC), kako bazalna tako i nakon ABBREVIATIONSAHDL -direct high-density cholesterol; ALB -albumin; ALP -alkaline phosphatase; ALT -alanine aminotransferase;AMY -amylase; AST -aspartate aminotransferase;bw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Lcystine is the main form of Cys because it is more stable when oxidized in physiological conditions. Cys is included in many metabolic reactions like protein synthesis, the generation of GSH, Tau, pyruvate and inorganic sulfur 66 and creatinine in rats compared to control 67 . Biochemical evaluation of liver and pancreatic function in condition of high Met intake showed lower concentrations of aspartate aminotransferase and alkaline phosphatase and higher serum amylase levels compared to control 67 .…”
Section: Cysteinementioning
confidence: 99%
See 1 more Smart Citation
“…Lcystine is the main form of Cys because it is more stable when oxidized in physiological conditions. Cys is included in many metabolic reactions like protein synthesis, the generation of GSH, Tau, pyruvate and inorganic sulfur 66 and creatinine in rats compared to control 67 . Biochemical evaluation of liver and pancreatic function in condition of high Met intake showed lower concentrations of aspartate aminotransferase and alkaline phosphatase and higher serum amylase levels compared to control 67 .…”
Section: Cysteinementioning
confidence: 99%
“…Cys is included in many metabolic reactions like protein synthesis, the generation of GSH, Tau, pyruvate and inorganic sulfur 66 and creatinine in rats compared to control 67 . Biochemical evaluation of liver and pancreatic function in condition of high Met intake showed lower concentrations of aspartate aminotransferase and alkaline phosphatase and higher serum amylase levels compared to control 67 . The ratio between Cys and L-cystine (its oxidized form) is very important in controlling oxidative stress and inflammatory response [68][69][70] .…”
Section: Cysteinementioning
confidence: 99%
“…It is important to note that amino acids are widely used in a variety of elds; these molecules are the basis of all vital processes because they are essential to the integrity of metabolic processes, and they are used in pharmaceutical and cosmetic applications (intermediates for the chemical industry), as well as in animal feed and food. 31,32 Since amino acids are the fundamental components of proteins and the source of many other compounds required by the body's organs, their presence is of utmost signicance and value. Because of this, there is a rising need for amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Methionine is defined as basic sulfur that contains important amino acid and is necessary for many vital activities necessary in the body, Methionine is considered a preventive agent for many liver damages, The daily amount of methionine that the body needs are 13 mg/ kg or one gram per day for adult humans ,The amino acid methionine is naturally present in animal-derived proteins such as beef, fish, poultry, eggs, and cheese, It is also present in juices, vegetables and sunflower seeds, crab meals, blood meals, gluten meals and tormented foods, as well as in fruit and casein and rice, which have been established as new sources of methionine or can be developed industrially in pharmaceutical preparation and nutritional supplements (Salman,2014) Studies have also shown that methionine is important for the body, but also that high levels of methionine in the food cause damage to the erythrocyte membrane and also trigger delays in tissue growth and injury, steatosis, hepatitis, hypertriglyceridemia and hepatotoxicity (Balkan et al, 2004). methionine one of the factors triggering a disorder of homocysteine metabolism and the accumulation of homocysteine in large amounts triggered by a case of hyperhomocysteinemia (HHcy) and other pathological conditions ,the risk factor for the digestive system, neurological diseases, strokes, arteriosclerosis, coronary artery inflammation and myocardial infarction involves congestive heart failure and coronary artery disease as well as Alzheimer's disease and type II diabetes and homocysteine (Micovic et al, 2016).…”
Section: Introductionmentioning
confidence: 99%